2002
DOI: 10.1007/s15010-002-2096-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Once-Daily Telithromycin Compared with High-Dose Amoxicillin for Treatment of Community-Acquired Pneumonia

Abstract: Telithromycin 800 mg once daily is a convenient, optimal-spectrum, first-line treatment for CAP in adults, at least as effective and well tolerated as high-dose amoxicillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 29 publications
3
44
0
5
Order By: Relevance
“…Gastrointestinal symptoms such as diarrhea were, therefore, the most commonly reported adverse events, and were usually judged by the investigator to be mild or moderate in intensity. Few patients discontinued the study because of intolerable adverse events, which supports the favorable tolerability of this agent observed in other studies [26][27][28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 80%
“…Gastrointestinal symptoms such as diarrhea were, therefore, the most commonly reported adverse events, and were usually judged by the investigator to be mild or moderate in intensity. Few patients discontinued the study because of intolerable adverse events, which supports the favorable tolerability of this agent observed in other studies [26][27][28][29][30][31][32].…”
Section: Discussionsupporting
confidence: 80%
“…The results of the present pooled analysis are consistent with the overall clinical and bacteriological efficacy (91.2 and 90.4%, respectively) observed in the trials of patients with CAP treated with a once-daily oral dose of telithromycin 800 mg [14,15,16,17,18,19,20]; Aventis,unpubl. data[].…”
Section: Discussionsupporting
confidence: 89%
“…This profile is accompanied by a low potential to select for, or induce, resistance among strains of gram-positive micro-organisms [12, 13]. A number of clinical trials have demonstrated clinical and bacteriological efficacy with telithromycin 800 mg once daily in patients with CAP that was equivalent to a panel of current standard treatments [14,15,16,17]. The present paper reports a pooled analysis of these and other studies of telithromycin in CAP to determine the efficacy of telithromycin specifically in patients with CAP caused by pneumococci with reduced susceptibility to penicillin and/or erythromycin.…”
Section: Introductionmentioning
confidence: 99%
“…[60][61][62][63][64][65][66][67][68][69] AECB More than 6% of US adults have AECB. 70 Approximately 50% of exacerbations are caused by typical bacteria (ie, S pneumoniae, H influenzae, and M catarrhalis).…”
Section: Capmentioning
confidence: 99%